ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI INDUSTRI TAPIOKA (Studi Kasus PT.Hutahaean Kec Laguboti, Kab Toba Samosir, Sumatera Utara) - Sibarani, Sako Sintya; Yusuf, Yusbar; Harahap, Azwar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to analize the effecting factors of production industrial tapioca (case study sub-district Laguboti, regency Toba Samosir, North Sumatera). The study use seconder data. The analytical method that used in this study are quantitative descriptive method, partial analysis and simultaneous (multiple regression analysis model with Cobb-Douglas production with the help of the program SPSS version 21). Based on the result of the test, the regression simultaneous test (f test) shows that all of independent variable has the significant effect for the production of tapioca. The partial regression test (t test) shows that the capital variable has positive and not significant effect with the koifisien value of 0.006, raw material cost variable has positive and significant effect with the koifisien value of 0.269, and the engine variable has positive and significant effect for the production of the tapioca with koifisien value of 0,665. The effect that caused (R2) by the three variables by simultaneous for the production variable of the tapioca 96,5% meanwhile the other 3,5% effected by the other variable that not mentioned on the model.Keywords: production, capital, cost , and engine